Is the labor market vulnerability of less-educated men really about job competition? New insights from the United States - Maurice Gesthuizen; Heike Solga (Journal for Labour Market Research, 2014)
There are various reasons why less-educated men have higher risks of labor market vulnerability - risks such as being unemployed or, if employed, having only low socioeconomic status. The commonly used argument is that these higher risks result from increased job competition caused by an oversupply of higher educated workers, who displace the less-educated from their jobs. In addition to exploring this argument, we investigate the impact of less-educated men's cognitive skills, their social resources, and the (historically embedded) signaling value of not having educational credentials. We study this impact by using institutional and compositional variations across labor market entry cohorts in the United States. For our analyses, we use the data of the 1974-2008 US General Social Survey (GSS). They show that an oversupply of high-educated workers mainly increases the unemployment risks of the higher-educated themselves. In labor market entry cohorts where the negative selection on parental background of the group of less-educated is more pronounced, the less-educated run a relatively high risk of unemployment.
Keywords: J20; L14; J24; I24; 330; Arbeitsmarktrisiko; Qualifikationsniveau; Niedrigqualifizierte; Niedriglohn; beruflicher Status; Wettbewerb; Arbeitskräfteangebot; kognitive Fähigkeit; soziales Netzwerk; soziale Faktoren; Arbeitslose; Statusinkonsistenz; Arbeitsmarktchancen; USA